Computer modelling of polarisome protein complex - Toh, Xia Ping (Nanyang Technological University, 2020)
Actin, a family of globular proteins found in the cells of most eukaryotes. Found in all eukaryotes but with little information known, researchers have looked more into it recently. Proteins such as Actin-Interacting Protein 5 (Aip5), Bud6 and Bni1 are some examples of what can be found within. Therefore, in this paper, I studied more about the interactions between the proteins through computer modelling software like GROMACS. The protein structures that have been derived will be put through Molecular Dynamics (MD) simulation for close observation in the natural states of the proteins in the absence of any external factors. The attached form due to the natural attractive nature of the side chains will then undergo umbrella sampling where pulling occur in a harmonic potential. Studies of the side chain interactions were done and comparison across the different protein chains were discussed in greater detail in this paper. It was proven that interaction between Aip5 and Bud6 were the strongest suggesting a strong relationship between the two. This could potentially pave the path for research surrounding Aip5, a rather unknown protein today. The reaction pathway of Actin in general is also a potential area for more studies.